Poverty, politics and plastic: Organic waste sorting in Blantyre's public markets - Wrixon Mpanang'ombe; Adrian Mallory; Elizabeth Tilley (Journal of Urban Management, 2021)
Similar to other poor countries across Africa, Malawi struggles with solid waste management (SWM). Especially considering the high proportion of organic waste, composting is a promising opportunity to tackle the problem. However, composting has had low uptake due to competing fertilizer subsidies, the perceived labour required, and a lack of training and equipment. Considering these issues, this paper presents an analysis of the political dynamics around SWM at markets in Blantyre, Malawi, and to understand how these dynamics may potentially affect the sorting of organic waste in order to improve the production of compost. We find complex systems of both formal and informal management that are deeply linked to the official political structures, creating a diverse array of actors with various vested interests. Implementing a separation program would need community engagement and long-term financial viability to ensure that the project is not abandoned as others have been. This paper contributes to understanding how the complexity of urban governance, combined with party politics, can affect the potential for introducing new models of waste management. It emphasises the importance of understanding both informal and formal management structures before designing interventions.
Keywords: 710; Malawi; Public markets; Organic waste; Composting; Management structures